2022
DOI: 10.1002/mrm.29475
|View full text |Cite
|
Sign up to set email alerts
|

NOE‐weighted imaging in tumors using low‐duty‐cycle2π‐CEST

Abstract: Purpose: Nuclear Overhauser enhancement (NOE)-mediated CEST imaging at −3.5 ppm has shown clinical interest in diagnosing tumors. Multiple-pool Lorentzian fit has been used to quantify NOE, which, however, requires a long scan time. Asymmetric analysis of CEST signals could be a simple and fast method to quantify this NOE, but it has contamination from the amide proton transfer (APT) at 3.5 ppm. This work proposes a new method using an asymmetric analysis of a low-duty-cycle pulsed-CEST sequence with a flip an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Summarily, the maps of T2 weighted anatomy and the AREXmfit APT display higher intensities in tumor tissues than in normal tissues while the maps of R1w, MT pool size ratio, AREXmfit NOE(-3.5 ppm), and AREXmfit MT show lower intensities; the maps of R1w, MT pool size ratio, AREXmfit NOE(-3.5 ppm), and AREXmfit MT show higher intensities in the corpus callosum than in the caudate putamen. Note that the previous studies have also demonstrated reduced NOE(-3.5 ppm) signals in the cancer tissues(12,17,18,39,(41)(42)(43)(44), which guarantees the reproducibility of our experiments.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Summarily, the maps of T2 weighted anatomy and the AREXmfit APT display higher intensities in tumor tissues than in normal tissues while the maps of R1w, MT pool size ratio, AREXmfit NOE(-3.5 ppm), and AREXmfit MT show lower intensities; the maps of R1w, MT pool size ratio, AREXmfit NOE(-3.5 ppm), and AREXmfit MT show higher intensities in the corpus callosum than in the caudate putamen. Note that the previous studies have also demonstrated reduced NOE(-3.5 ppm) signals in the cancer tissues(12,17,18,39,(41)(42)(43)(44), which guarantees the reproducibility of our experiments.…”
supporting
confidence: 75%
“…For all phantom imaging, f m was set to 0 due to the low MT pool size ratio. The AREX determined semi-solid MT effect was obtained by R 1 W L MT /(1 – L MT ), where L MT is the Lorentzian line for the MT effect (39). The AREXmfit quantified APT and NOE(−3.5 ppm) values were obtained by choosing the maximum value between 4 ppm and 3 ppm in the fitted APT spectra and between −3 ppm and −4 ppm in the fitted NOE(−3.5 ppm) spectra, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Summarily, the maps of T 2 weighted anatomy and the AREX mfit APT display higher intensities in tumor tissues than in normal tissues while the maps of R 1 w , MT pool size ratio, AREX mfit NOE (−3.5 ppm), and AREX mfit MT show lower intensities; the maps of R 1 w , MT pool size ratio, AREX mfit NOE (−3.5 ppm), and AREX mfit MT show higher intensities in the corpus callosum than in the caudate putamen. Note that the previous studies have also demonstrated reduced NOE (−3.5 ppm) signals in the cancer tissues, 12,17,18,39,41–44 which guarantees the reproducibility of our experiments.…”
Section: Resultssupporting
confidence: 78%
“…Cui et al also compared CEST signals acquired using CW-and pulsed-saturation schemes to filter out unwanted components. 78 Note that the simulations in Figures 2, 4, and 7 were performed using custom-written scripts in Python and the code can be downloaded from a public repository, https://github.com/ChongxueBie/RF-labeling-techniques-in-CEST-MRI. The simulations in Figures 5 and 6 were performed on MATLAB 2022b using source code downloaded from https://github.com/kherz/pulseq-cest-library.…”
Section: Saturation-based Editing Techniquesmentioning
confidence: 99%
“…For example, Jin et al developed the “average saturation efficiency filter” (ASEF) method, which utilizes these saturation parameters to achieve exchange rate filtering, 76,77 separating out signals of intermediate‐exchanging protons from fast‐exchanging protons and MTC. Cui et al also compared CEST signals acquired using CW‐ and pulsed‐saturation schemes to filter out unwanted components 78 …”
Section: Saturation‐based Labelingmentioning
confidence: 99%